2011
DOI: 10.1007/s10461-011-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Surveillance Study: Sexual Risk Taking Behaviour in UK HIV Outpatient Attendees

Abstract: This study aimed to determine demographic, behavioural and self-report disease/treatment variables among HIV-infected individuals (n = 666) that predict unprotected intercourse with a partner of unknown/discordant status. Sexual risk behaviour was reported by 12.8%. In multivariable analysis, risk was more likely to be reported by gay men compared to women or heterosexual men, and for those with higher psychological symptom burden. Psychological symptoms should be assessed and managed in the HIV outpatient set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…The data from this sample support previous findings that greater psychological symptom burden is associated with risk taking Harding, Clucas et al, 2011). A prior study from HIV outpatients in Buenos Aires found an association between depressive symptoms and risk (Segura et al, 2007), and our data reveal that the self-reported burden of psychological symptoms, which is a person-centred measure different from a measure of prevalence or diagnosis, is also relevant in managing risk behaviours.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The data from this sample support previous findings that greater psychological symptom burden is associated with risk taking Harding, Clucas et al, 2011). A prior study from HIV outpatients in Buenos Aires found an association between depressive symptoms and risk (Segura et al, 2007), and our data reveal that the self-reported burden of psychological symptoms, which is a person-centred measure different from a measure of prevalence or diagnosis, is also relevant in managing risk behaviours.…”
Section: Discussionsupporting
confidence: 87%
“…As the Global Distress Index includes items from both the Physical and Psychological Distress Indices, the Global Distress Index was not entered into the multivariable model. The Psychological Distress Index was forced into the model as a prior correlate of risk with items present in the Global Distress Index (Harding, Clucas et al, 2011;Valverde et al, 2009). Cases with missing data were excluded from the multivariable models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unsafe sexual practices among MSM have been on the rise in several European countries 14,15,16,17 but the related contexts and associated factors remain largely understudied in Portugal. The Internet has become a popular way for MSM to meet sexual partners throughout the continent, which in turn has been associated with risk behaviors 18,19,20 .…”
Section: Introductionmentioning
confidence: 99%